(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article considers the main issues of organizing public sports and leisure activities with the population. Sport-public affairs means a set of measures for the organization of public sports events, the main tasks of which are the organization of entertainment events with physical training and sports equipment.